Assembly language for x86 processors - Irvine, Kip R., 1951- (Pearson Education Limited, 2015)
This book is still focused on its primary goal, to teach students how to write and debug programs at the machine level. It will never replace a complete book on computer architecture, but it does give students the first-hand experience of writing software in an environment that teaches them how a computer works. Our premise is that students retain knowledge better when theory is combined with experience. In an engineering course, students construct prototypes; in a computer architecture course, students should write machine-level programs. In both cases, they have a memorable experience that gives them the confidence to work in any OS/machine-oriented environment.